1994
DOI: 10.1016/0014-5793(94)80603-9
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and regional distribution of a novel member of the opioid receptor family

Abstract: We have cloned a cDNA for a novel member of the opioid receptor family, designated as ROR-C, from the rat cerebrum cDNA library using the probe derived from the dopioid receptor subtype cDNA. The deduced amino acid sequence of ROR-C shows high homology with those of ROR-A (rat S-opioid receptor subtype), ROR-B (rat ,&subtype) and ROR-D (rat K-subtype). RNA blot hybridization and in situ hybridization analysis revealed that ROR-C mRNA is expressed in discrete regions of the rat centraf nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
187
0
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(207 citation statements)
references
References 27 publications
14
187
0
4
Order By: Relevance
“…Like (x, 8, and K opioid receptors, the newly discovered ORLi is also widely expressed throughout the brain and spinal cord as detected by Northern blotting, in situ hybridization and immunohistochemistry [2,3,5,18]. The expression of ORLi overlaps with that of other opioid receptors in many regions of the central nervous system.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Like (x, 8, and K opioid receptors, the newly discovered ORLi is also widely expressed throughout the brain and spinal cord as detected by Northern blotting, in situ hybridization and immunohistochemistry [2,3,5,18]. The expression of ORLi overlaps with that of other opioid receptors in many regions of the central nervous system.…”
Section: Discussionmentioning
confidence: 93%
“…These opioid receptors are all coupled to the inhibitory G protein (Gi) and negatively regulate adenylyl cyclase [1]. Recently, another Gi protein coupled receptor, opioid receptor-like receptor (ORLi), has been cloned from brain [2][3][4][5][6][7][8]. Its endogenous specific agonist nociceptin/orphanin FQ (OFQ) has also been identified [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the three major types of opioid receptors, μ, δ and κ (review in [1]), a novel receptor (ORLi, opioid receptor-likei) was identified on the basis of its homology with the amino acid sequence of opioid receptors [2][3][4][5][6][7][8]. The ORLi receptor has a very low affinity for traditional opioid peptides (dynorphins, endorphins, and enkephalins).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, nociceptin/orphanin FQ exhibits a nanomolar affinity for the ORLi receptor and a low affinity for the μ, δ, κ opioid receptors despite the presence in N-terminal position of the FGGF sequence instead of YGGF in endogenous opioid receptor ligands. Although the functional role of nociceptin/orphanin FQ remains unknown, the wide distribution of ORLi mRNA and nociceptin/orphanin FQ precursor in the central nervous system of rodents, particularly in the limbic system and in several areas known to be involved in the control of nociceptive stimuli, including the spinal cord dorsal horn, have suggested that this peptide could be involved in pain perception [2][3][4][5][11][12][13]. The peptide has been reported to heighten sensitivity to pain following i.c.v.…”
Section: Introductionmentioning
confidence: 99%
“…The NOP receptor is a G-protein-coupled receptor with a high degree of structural homology to classical opioid receptors [11,30]. Despite the high degree of sequence similarity between N/OFQ and opioid peptides (as dynorphin A), N/OFQ does not interact with µ-, d-or k-opioid receptors, and opioid peptides do not interact with the NOP receptor [5].…”
Section: Introductionmentioning
confidence: 99%